Seblang Dance's Cultural Semantics: Conserving the Oseng Tribe to Promote Banyuwangi's Cultural Tourism - Mukarromah, Inayatul; Qomariyah, Dewi Nurul; Hayuningtyas, Nina; Khodijah, Siti; Lindayani, Lilik Rita (SAWERIGADING, 2025)
This study aims to identify the semiotic meaning embedded in each ornament worn by Seblang dancer and contribute substantially to the Oseng language and tribe, preserving this culture is closely related to the growth of Banyuwangi's tourism industry.  The phases of gathering data are observation interviews, and documentation. This study employed data analysis techniques from the interactive model of Miles and Huberman (Miles Huberman, 2015), which includes data collection, data reduction, data presentation, and conclusion. The results of the research on the semiotic perspective and multimodal Seblang dance reveal that it functions as both a cultural symbol performance to support Tourism industry as heritage cultural tourism. It is aesthetically packaged and presented to attract international and domestic tourists. AbstrakPenelitian ini bertujuan untuk mengidentifikasi makna semiotik yang terkandung dalam setiap ornamen yang dikenakan oleh penari Seblang dan memberikan kontribusi yang signifikan bagi bahasa dan suku Oseng, pelestarian budaya ini erat kaitannya dengan perkembangan industri pariwisata Banyuwangi.  Fase pengumpulan data dilakukan dengan pengamatan, wawancara, dan dokumentasi. Penelitian ini menggunakan teknik analisis data dari model interaktif Miles dan Huberman (Miles Huberman, 2015), yang meliputi pengumpulan data, pengurangan data, penyajian data, dan kesimpulan. Hasil penelitian dari perspektif semiotik dan multimodal tarian Seblang menunjukkan bahwa tarian ini berfungsi sebagai simbol budaya dan pertunjukan yang bertujuan untuk meningkatkan industry pariwisata sebagai budaya warisan. Tarian ini dikemas dan disajikan secara estetis untuk menarik wisatawan internasional dan domestik.